The future of tic disorder treatment. (31st October 2013) - Bennett, Shannon M.; Keller, Alex E.; Walkup, John T.
Abstract : Competing theories on the etiology and treatment of chronic tic disorders and Tourette syndrome have long made the search for efficacious intervention more challenging for patients and families seeking to reduce functional impairment related to tic symptoms. These symptoms were historically posited to be either psychological in origin, leading to the long tradition of psychoanalytic psychotherapy for tics, or biological in nature, particularly since the advent of successful treatments using neuroleptic medications. Current thinking about the phenomenology of tic disorders comes from growing empirical evidence as well as advances in neuroscience and genetics research and reveals a biological vulnerability that is exacerbated by physiological arousal related to environmental or interpersonal stress. This manuscript summarizes the evolution of this knowledge base and describes current best‐practice recommendations for patients, families, and clinicians.